Strengthening Election Regulations: Saving Democracy from The Threat of Political Money in Indonesia - Raihan Hafiz Ramadhan; Aidul Fitriciada Azhari (Universitas Muhammadiyah Surakarta, 2023)
General elections are the cornerstone of a democratic system. However, in Indonesia, the practice of money politics poses a serious threat to the integrity of elections and political justice. This article aims to analyze the importance of strengthening electoral regulations to combat money politics and provide steps that can be taken to safeguard democracy from such practices. The research methodology employed in this study focuses on analyzing existing legislation, government regulations, electoral institution decisions, and court rulings related to elections and money politics. The results and discussion of this article include concrete measures that can be taken to strengthen electoral regulations and combat money politics in Indonesia. These measures encompass increasing transparency and financial reporting, limiting campaign expenditures, enforcing strict legal measures, educating and raising awareness among the public, monitoring media and campaigns, fostering active public participation, and improving the political financing system. By strengthening electoral regulations, democracy in Indonesia can be protected from the threat of money politics. These steps will create a fair, transparent, and just political environment where the public interest is prioritized. Active participation of the public in elections and strict law enforcement against violations related to money politics are also crucial in preventing such practices. In conclusion, this article highlights the importance of strengthening electoral regulations in safeguarding democracy from the threat of money politics in Indonesia. By enhancing transparency, imposing limits on campaign expenditures, enforcing strict legal measures, educating the public, monitoring the media, encouraging public participation, and reforming the political financing system, Indonesia can build a more fair, transparent, and democratic electoral system.